Psychometric Evidence of a Measure of General Self-Efficacy in Peruvian Schoolchildren: Internal Structure, Reliability and Factorial Invariance and Proposal of a Brief Version - Arias Gallegos, Walter L. (2024)
The present research aims to propose a brief version of a measure of general self-efficacy, based on the Self-Efficacy Scale, and to evaluate its evidence of validity based on internal structure, reliability and factorial invariance according to sex. A total of 806 students (67.5% male and 32.5% female) of secondary level from 13 educational institutions in the city of Arequipa (Peru) participated. The data were processed using Confirmatory Factor Analysis and Item Response Theory. The results indicate that the original 20-item version of the 10-item Brief Alegre Self-Efficacy Scale is unidimensional with adequate goodness-of-fit and reliability indices (ω =.89). In addition, the presence of factorial invariance between males and females was tested. It is concluded that the proposed measure is valid and reliable, with a monotonic level of difficulty. However, more research is needed with representative samples and with respect to other educational variables.